The interplay between cardiac dyads and mitochondria regulated the calcium handling in cardiomyocytes - Liu, Lei; Zhou, Kaiyu; Liu, Xiaoliang; Hua, Yimin; Wang, Hua; Li, Yifei (Frontiers in Physiology, 2022)
Calcium mishandling and mitochondrial dysfunction have been increasingly recognized as significant factors involved in the progression procedure of cardiomyopathy. Ca2+ mishandling could cause calcium-triggered arrhythmias, which could enhance force development and ATP consumption. Mitochondrial disorganization and dysfunction in cardiomyopathy could disturb the balance of energy catabolic and anabolic procedure. Close spatial localization and arrangement of structural among T-tubule, sarcoplasmic reticulum, mitochondria are important for Ca2+ handling. So that, we illustrate the regulating network between calcium handling and mitochondrial homeostasis, as well as its intracellular mechanisms in this review, which would be worthy to develop novel therapeutic strategy and restore the function of injured cardiomyocytes.